Macroplastic Fragment Contamination of Agricultural Soils Supports a Distinct Microbial Hotspot - McKay, Olivia; Pold, Grace; Martin, Philip; Sistla, Seeta (Frontiers in Environmental Science, 2022)
Agricultural plastics support crop production and quality by reducing weeds, improving irrigation efficiency, and regulating soil conditions, but can also become a soil pollutant. While microplastic effects on soil function are increasingly well-understood, the impacts of agricultural macroplastic (> 5 mm) contamination on soils are poorly documented. Prolonged exposure to plastic macrofragments may alter microbial decomposer community structure and function, since plastic can directly affect edaphic factors while leaching novel compounds. To better characterize how plastic contamination influences the soil habitat, we sampled three farms characterized by agricultural plastic pollution in Monterey County, CA, USA. Using a randomized block design, we collected surface soil samples from the fields (“bulk PC soil”) to compare with soil directly in contact with the remaining polyethylene (PE) mulch and polyvinyl chloride (PVC) dripline fragments (“plastic-associated soil”). Soil directly associated with plastic fragments was hypothesized to have reduced microbial biomass and decomposer activities relative to the bulk soil, due to a greater likelihood of toxicity. In contrast to our expectations, we found that both PE and PVC macrofragments support a distinct microbial habitat that hosts a larger, more efficient microbial biomass with greater labile nutrient pools than the surrounding bulk soil. Because of the scope of macroplastic pollution likely occurring in agricultural soils, our findings suggest that this novel plastisphere habitat may significantly alter ecological functions critical to agricultural soils over time by encouraging microbial colonization within plastic debris.